MEMORIA HISTORICA DE LA EDAD MEDIA E IDEA DE TRADICION EN MENENDEZ PIDAL Y APMERICO CASTRO (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
This article deals with the philosophical background of the confusion between memory and historical truth and its consequences to the Hispanic Medieval studies. With this purpose, we analyse the concept of tradition in the Ramón Menéndez Pidal and Américo Castro essays about the historical Hispanic reality whose main reference is the medieval culture. Memory and Life are basic concepts in this article. Memory because it is showed by both authors as the common root of literature and history, Life because it seems their central argument to unify juridical and literary traditions. We aim to argue that the cultural and historical memory of this traditionalism is a result of the confusion between the time of the literary tradition and the time of a hypothetical common experience.